Self-regulatory mechanisms of doping intentions in elite athletes: The role of self-determined motivation in sport - Corrion, K.; Scoffier-Mériaux, S.; Longueville, F. (Journal of Sports Medicine & Doping Studies, 2017)
Objective: Although research on the personal and psychosocial predictors of doping has been extensive, the factors related to the socio-cognitive self-regulatory mechanisms of doping remain unexplored. The aim of this study was to test an integrated multi-theory model examining the role of self-determined motivation in sport in the self-regulatory mechanisms of doping intentions in elite athletes.